Health Insurance in Nepal: Premium-claim Imbalance, Equity Gaps, and the Challenge of Achieving Universal Coverage - Vaidya, Rashesh (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: The study examines Nepal’s health insurance performance, focusing on enrollment, premium collection, and claims disbursement, identifying operational and policy barriers affecting sustainability and equity. Design/methodology/approach: A descriptive study analyzed secondary data (2015–2024) from Nepal’s Health Insurance Board, using percentage-based trend analysis of insured citizens, premium collected, claim paid, and premium-claim ratio under Universal Health Coverage (UHC). Findings: Nepal’s health cover has grown rapidly since F/Y 2015-16, enhancing universal health cover but at the cost of gender and marginal group equity gaps. COVID-19 caused claim spikes and financial instability, though premiums bounced back in F/Y 2023-24. Despite higher utilization, satisfaction remains moderate due to service gaps. Regional disparities in health security access are evident in Social Health Security Program (SHSP) enrollment trends. The Health Insurance Board needs an urgent reform in premium pricing to ensure longevity of the policy. Conclusion: Nepal’s insurance scheme faces systemic inefficiencies, with an unsustainable premium-claim ratio (331.3 percent in F/Y 2023-24) and irregular enrollments across provinces, undermining UHC. To improve retention and equity, streamlined processes, awareness campaigns, and policy reforms are urgently needed to ensure financial stability and equitable access. Implications: To attain fair UHC, Nepal must address regional disparities, maintain financial stability, and advance inclusive policies. Originality/Value: The study assesses Nepal’s health insurance system, revealing inequalities and financial instability, providing policy recommendations for gendersensitive reforms and crisis preparedness strategies. JEL Classification: I13, I18, H51